2020
DOI: 10.3390/plants9111442
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A Affects Developmental Reprogramming of Bread Wheat Microspores towards an Embryogenic Route

Abstract: Microspores can be developmentally reprogrammed by the application of different stress treatments to initiate an embryogenic pathway leading to the production of doubled haploid (DH) plants. Epigenetic modifications are involved in cell reprogramming and totipotency in response to stress. To increase microspore embryogenesis (ME) efficiency in bread wheat, the effect of the histone deacetylase inhibitor trichostatin A (TSA) has been examined in two cultivars of wheat with different microspore embryogenesis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 79 publications
(115 reference statements)
4
21
0
Order By: Relevance
“…Therefore, it could be assumed that a higher abundance of actin filaments (AF) in winter triticale anthers was not required for high ME effectiveness. Similar conclusions, based on AF depolymerization associated with elevated Ca 2+ levels, observed in embryogenic microspores of oilseed rape and wheat, were drawn by Gervais et al 45 and Castillo et al 46 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, it could be assumed that a higher abundance of actin filaments (AF) in winter triticale anthers was not required for high ME effectiveness. Similar conclusions, based on AF depolymerization associated with elevated Ca 2+ levels, observed in embryogenic microspores of oilseed rape and wheat, were drawn by Gervais et al 45 and Castillo et al 46 .…”
Section: Discussionsupporting
confidence: 84%
“…Expression of this gene was induced in wheat zygotic embryos 56 and in wheat anthers on the 5 th day of in vitro culture 13 . Moreover, an increased transcript level of this gene was observed after treatment with histone deacetylase inhibitor (trichostatin A, TSA) on the 3 rd day of culture in two bread wheat cultivars with different androgenic response 46 . Similarly, its up-regulation was observed in triticale anthers after 4 days of in vitro culture 12 , and in triticale microspores after ME-inducing low temperature treatment 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Golden Promise; GP), it can be speculated that MAN may also participate in epigenetic processes, inhibiting the activity of the enzymes involved in the synthesis of SAM (our unpublished results). Our interpretation is partially supported by the work of Castillo et al (2020), who found that the histone deacetylase inhibitor trichostatin A (TSA) together with MAN treatment led to microspore reprogramming, increased the number of embryogenic microspores and regenerated green plants in bread wheat. However, this hypothesis needs to be further investigated.…”
Section: Cysteine-rich Tripeptide (Glutathione)supporting
confidence: 65%
“…If they were used, it was mainly as a treatment within plant tissue cultures. Specifically, the use of Trichostatin A induced microspore embryogenesis in wheat [ 142 ] and somatic embryogenesis in Arabidopsis [ 143 ]. Treatment by trichostatin A and sodium butyrate also improved regeneration efficiency from mature wheat embryos [ 144 ].…”
Section: Epigenetic Advances In Crop Improvement: Exploiting Epigenetic Diversitymentioning
confidence: 99%
“…Recent advances in chemically controlled mammalian cell reprogramming have shown the high potential of application of synthetic small molecules, including epigenetic inhibitors, to control cellular reprogramming, proliferation, and differentiation, as well as cancer cell reprogramming [ 291 , 292 ]. In plants, epigenetics chemical targeting with inhibitors of DNA methylation (5-AzaC, Zebularine), H3K9 methylation (BIX-01294), or histone deacetylases (Trichostatin A, Suberoylanilide hydroxamic acid, SAHA) has been demonstrated to improve in vitro plant cell reprogramming and regeneration, to produce DHs, and to propagate selected clonal plants in a number of crop and forest species, such as rapeseed, barley, wheat, and cork oak [ 128 , 142 , 284 , 286 , 293 , 294 ].…”
Section: Gaps In Knowledge and Future Challengesmentioning
confidence: 99%